The Effect of Using Peer Reviewing Technique in Writing Skill (Journal of the College of Basic Education, 2026)
Writing is the most important skills and holds a significant place in teaching English as a foreign language. Teaching English is not simply about teaching writing skills, but rather about developing a new language. Given the educational indicators suggesting a weakness in writing skills among English language learners, the current study aims to investigate "the effect of peer reviewing technique in writing skills". To achieve the goal of this research, the following hypothesis was proposed: "There are no statistically significant differences between all participating students in the pre- and post-tests of the experimental and control groups in writing skill. To verify the initial hypothesis, the current research followed pre and posttest. The group of (72) was tested by pretest. Students selected from the evening studies in the English Department at the College of Basic Education. The face validity of the test was confirmed by presenting it to a group of language teaching specialists in methods of teaching and linguistics.